Land use and mobility during the Neolithic in Wales explored using isotope analysis of tooth enamel. Issue 2 (28th July 2017) - Neil, Samantha; Montgomery, Janet; Evans, Jane; Cook, Gordon T.; Scarre, Chris
Abstract: Objectives: The nature of land use and mobility during the transition to agriculture has often been debated. Here, we use isotope analysis of tooth enamel from human populations buried in two different Neolithic burial monuments, Penywyrlod and Ty Isaf, in south‐east Wales, to examine patterns of land use and to evaluate where individuals obtained their childhood diet. Materials and Methods: We employ strontium ( 87 Sr/ 86 Sr) and oxygen (δ 18 O) and carbon (δ 13 C) isotope analysis of enamel from adjacent molars. We compare strontium isotope values measured in enamel to locally bioavailable 87 Sr/ 86 Sr values. We combine discussion of these results with evaluation of new radiocarbon dates obtained from both sites. Results: The majority of enamel samples from Penywyrlod have strontium isotope ratios above 0.7140. In contrast, the majority of those from Ty Isaf have 87 Sr/ 86 Sr values below 0.7140. At Penywyrlod oxygen isotope ratios range between 25.9 and 28.2 ‰ (mean 26.7 ± 0.6 ‰, 1σ, n = 15) and enamel δ 13 Ccarbonate values range between −18.0 and −15.0 ‰ (mean −16.0 ± 0.8 ‰, 1σ, n = 15). At Ty Isaf oxygen isotope ratios exhibited by Neolithic individuals range between 25.4 and 27.7 ‰ (mean 26.7 ± 0.6 ‰, 1σ, n = 15) and enamel δ 13 Ccarbonate values range between −16.9 and −14.9 ‰ (mean −16.0 ± 0.6 ‰, 1σ, n = 15). Discussion: The strontium isotope results suggest that the majority of individuals buried at Penywyrlod did not source their childhood diet locally. One individual in this group has strontium isotope ratios that exceed all current known biosphere values within England and Wales. This individual is radiocarbon dated to the first few centuries of the 4 th millennium BC, consistent with the period in which agriculture was initiated in Wales: the results therefore provide evidence for migration during the transition to farming in Wales. In contrast, all individuals sampled from Ty Isaf post‐date the period in which agriculture is considered to have been initiated and could have sourced their childhood diet from the local region in which they were buried.